Original paperA new two-step accurate CT-MRI fusion technique for post-implant prostate cancer - Kunogi, Hiroaki; Hojo, Hidehiro; Wakumoto, Yoshiaki; Saito, Anneyuko I.; Ishikura, Satoshi; Yamashiro, Yuki; Kuwatsuru, Ryouhei; Sasai, Keisuke (Journal of Contemporary Brachytherapy, 2015)
Purpose: To develop an accurate method of fusing computed tomography (CT) with magnetic resonance imaging (MRI) for post-implant dosimetry after prostate seed implant brachytherapy. Material and methods: Prostate cancer patients were scheduled to undergo CT and MRI after brachytherapy. We obtained the three MRI sequences on fat-suppressed T1-weighted imaging (FST1-WI), T2-weighted imaging (T2-WI), and T2*-weighted imaging (T2*-WI) in each patient. We compared the lengths and widths of 450 seed source images in the 10 study patients on CT, FST1-WI, T2-WI, and T2*-WI. After CT-MRI fusion using source positions by the least-squares method, we decided the center of each seed source and measured the distance of these centers between CT and MRI to estimate the fusion accuracy. Results : The measured length and width of the seeds were 6.1 ± 0.5 mm (mean ± standard deviation) and 3.2 ± 0.2 mm on CT, 5.9 ± 0.4 mm, and 2.4 ± 0.2 mm on FST1-WI, 5.5 ± 0.5 mm and 1.8 ± 0.2 mm on T2-WI, and 7.8 ± 1.0 mm and 4.1 ± 0.7 mm on T2*-WI, respectively. The measured source location shifts on CT/FST1-WI and CT/T2-WI after image fusion in the 10 study patients were 0.9 ± 0.4 mm and 1.4 ± 0.2 mm, respectively. The shift on CT/FST1-WI was less than on CT/T2-WI (p = 0.005). Conclusions : For post-implant dosimetry after prostate seed implant brachytherapy, more accurate fusion of CT and T2-WI is achieved if CT and FST1-WI are fused first using the least-squares method and the center position of each source, followed by fusion of the FST1-WI and T2-WI images. This method is more accurate than direct image fusion.